PENGARUH LIKUIDITAS, SOLVABILITAS, PROFITABILITAS TERHADAP HARGA SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Novita Permatasari; Suratna .; Meilan Sugiarto (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2019)
This study aims to determine the influence of Liquidity from Current Ratio (CR), Solvability from Debt to Equity Ratio (DER) and Profitability from Return On Investment (ROI) to Stock Prices with Corporate Value of Book Value (PBV) as a intervening variables. Infrastructure, transportation and transportation service companies provided on the Indonesia Stock Exchange in 2011-2017 as research sample. Sampling technique using purposive sampling which then obtained a sample of 10 companies in the infrastructure, utilities and transportation sectors. The research data uses secondary data, namely the company's annual financial statements during 2011-2017 obtained from the Indonesia Stock Exchange (IDX) and the company's official website. The analytical method used is path analysis (path analysis) using the PLS program SmartPLS 3.2.8 application. Liquidity and Profitability do not have a significant effect on Stock Prices while Solvability and Company Value influence significantly on Stock Prices. The Liquidity Value is not significant to the Firm Value but Solvability and Profitability significantly influence the Firm Value. Liquidity does not have a significant effect on Stock Prices through Company Value. While Profitability and Solvability have a significant effect on Stock Prices through Corporate Value. Keywords: liquidity, solvability, profitability, firm value, stock price.